2015
DOI: 10.1007/s11095-015-1646-x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Oral Bioavailability of N-251, a Novel Antimalarial Drug, by Increasing Lymphatic Transport with Long-Chain Fatty Acid-Based Self-Nanoemulsifying Drug Delivery System

Abstract: SNEDDS formulations significantly improved the absorption behavior of N-251 and long-chain fatty acid-based lipid further improved it by avoiding the hepatic first-pass elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…This study suggested that co-administration with LCT promotes transport via the lymphatic pathway relative to co-administration with MCT or LCT. Other researchers have also observed increased bioavailability of PWS drugs using LCT due to enhanced lymphatic transport [115]. The solubility of the drug in lipid is also a factor in lymphatic transport.…”
Section: Key Processes Governing Lipid Impact On Overall Oral Absomentioning
confidence: 98%
“…This study suggested that co-administration with LCT promotes transport via the lymphatic pathway relative to co-administration with MCT or LCT. Other researchers have also observed increased bioavailability of PWS drugs using LCT due to enhanced lymphatic transport [115]. The solubility of the drug in lipid is also a factor in lymphatic transport.…”
Section: Key Processes Governing Lipid Impact On Overall Oral Absomentioning
confidence: 98%
“…Literature reveals that the nanoparticles are being explored for drug delivery of antimalarial drugs which include pheroids, 84 lipososmes, 85 solid lipid nanoparticles, 86 polymer-lipid nanoparticles, 87 dendrimers, 88 polymeric nanoparticles, 89 self-emulsifying drug delivery systems 90 for antimalarial drugs. In recent years, hydrogels based systems for antimalarial drugs are also being explored which have shown decent results.…”
Section: Hydrogel Based Systems For Malariamentioning
confidence: 99%
“…Pharmacokinetics in animal studies is required to forward the development of N-251, which is a drug that can be of practical use. Although we have already started the additional study about the improvement of the bioavailability ( F ) of N-251 in non-infected rats [16], a pharmacokinetic (PK) analysis was performed under various conditions in mice, which included dose dependency, influence of diet, parasite infection, and number of administrations. In addition, the appropriate administration schedule for achieving the complete curative effect of N-251 against P. berghei in mice has already been determined [12].…”
Section: Introductionmentioning
confidence: 99%